Two new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the Shevaroy massif, Tamil Nadu, India, with a preliminary ND2 phylogeny of Indian Cnemaspis - Khandekar, Akshay; Gaitonde, Nikhil; Agarwal, Ishan (Zootaxa, 2019)
We present a preliminary ND2 phylogeny of South Asian Cnemaspis, recovering a number of deeply divergent clades within Indian Cnemaspis, endemic to the southern and northern Western Ghats besides the Mysore Plateau and hills of Tamil Nadu. There are a number of unnamed lineages that are >5% divergent on ND2 across the phylogeny, including three from the gracilis clade on an elevation gradient (800–1400 m asl.) around Yercaud in the Shevaroy massif, Salem district, Tamil Nadu. We describe two of these as new species— Cnemaspis shevaroyensis sp. nov. and Cnemaspis thackerayi sp. nov. are both allied to Cnemaspis gracilis and can be diagnosed from all other Indian Cnemaspis by the absence of spine-like scales on flank, heterogeneous dorsal pholidosis, presence of femoral and precloacal pores, tail with enlarged, strongly keeled, conical tubercles forming whorls, a median row of enlarged and smooth sub-caudals. They differ from C. gracilis and each other in body size, the number of tubercles around midbody, the number of tubercles in paravertebral rows, the number of femoral and precloacal pores, the number of poreless scales in-between precloacal pores and between femoral and precloacal pores, and subtle colour pattern differences; besides uncorrected mitochondrial sequence divergence (7.9–16.6 %). We also provide a description of Cnemaspis yercaudensis from its type locality and an additional locality. The discovery of two endemic species and a third unnamed divergent lineage from an isolated massif in peninsular India outside the Western Ghats indicate that many other such understudied hill ranges may harbour high endemic biodiversity.